Sedentary Behaviors and Physical Activity Habits Independently Affect Fat Oxidation in Fasting Conditions and Capillary Glucose Levels After Standardized Glucose-Rich Meal in Healthy Females - Tabozzi, Sarah A.; Di Santo, Simona G.; Franchini, Flaminia; Ratto, Federica; Luchi, Matilde; Filiputti, Beatrice; Ardigò, Luca P.; Lafortuna, Claudio L. (Frontiers in Physiology, 2020)
Purpose: Sedentary behaviours and muscle inactivity are being growingly recognised as important risk factors for health, adjunctively and independently from a scarce physical activity, although it is barely clear the metabolic mechanism underneath. To explore the relation between sedentary behaviours and metabolism, we measured the metabolic profile in fasting condition and after oral glucose overload in a group of women, along with objective monitoring and subjective reporting of their physical activity/sedentary lifestyle habits. Subjects and methods: Thirteen women (age: 32.5±16.1 yrs.; BMI: 24.0±3.3 kg/m2), recruited among university students and research staff, underwent indirect calorimetry to assess fat and carbohydrate contribution to energy metabolism, in fasting conditions and after a glucose-rich standard meal (about 45g glucose). Glucose concentration in capillary blood was determined in fasting state and 15 and 30 min after meal. Habitual physical activity and sedentary behaviours in the previous week were continuously monitored with Actigraph accelerometers and subjectively reported through IPAQ questionnaire. Results: After adjustment for age, the contribution of fat oxidation to metabolic energy sources in fasting conditions resulted significantly correlated with time spent in sitting/lying position during wake hours (p = 0.013), independent from physical activity habits, whereas capillary blood peak glucose concentration after the meal was significantly and inversely correlated with average daily MVPA (p = 0.025), independent from average daily sitting/lying time. The parameters from subjective reporting failed to provide significant correlation concerning the metabolic effects of sedentary habits, though confirmed the effect of physical activity on capillary glucose peaks after the meal. Conclusions: Here we report for the first time a direct effect of muscle inactivity on increased fat oxidation in fasting conditions, which can be hypothesised as a preliminary condition for the development of insulin resistance. We also report the direct independent effect of physical activity on the capacity to respond to a glycaemic load, so that sedentary behaviours and reduced physical activity appear to concur, although independently, to the increased health risk, as elsewhere observed on an epidemiological ground.